Anti‐tumor effects of suberoylanilide hydroxamic acid on Epstein–Barr virus‐associated T cell and natural killer cell lymphoma. Issue 6 (13th May 2014) - Siddiquey, Mohammed N.A.; Nakagawa, Hikaru; Iwata, Seiko; Kanazawa, Tetsuhiro; Suzuki, Michio; Imadome, Ken‐Ichi; Fujiwara, Shigeyoshi; Goshima, Fumi; Murata, Takayuki; Kimura, Hiroshi
<x xml:space="preserve">Abstract</x> The ubiquitous Epstein–Barr virus (EBV) infects not only B cells but also T cells and natural killer (NK) cells and is associated with various lymphoid malignancies. Recent studies have reported that histone deacetylase (HDAC) inhibitors exert anticancer effects against various tumor cells. In the present study, we have evaluated both the in vitro and in vivo effects of suberoylanilide hydroxamic acid (SAHA), an HDAC inhibitor, on EBV‐positive and EBV‐negative T and NK lymphoma cells. Several EBV‐positive and EBV‐negative T and NK cell lines were treated with various concentrations of SAHA. SAHA suppressed the proliferation of T and NK cell lines, although no significant difference was observed between EBV‐positive and EBV‐negative cell lines. SAHA induced apoptosis and/or cell cycle arrest in several T and NK cell lines. In addition, SAHA increased the expression of EBV‐lytic genes and decreased the expression of EBV‐latent genes. Next, EBV‐positive NK cell lymphoma cells were subcutaneously inoculated into severely immunodeficient NOD/Shi‐scid/IL‐2Rγnull mice, and then SAHA was administered intraperitoneally. SAHA inhibited tumor progression and metastasis in the murine xenograft model. SAHA displayed a marked suppressive effect against EBV‐associated T and NK cell lymphomas through either induction of apoptosis or cell cycle arrest, and may represent an alternative treatment option.